Prospective Association Between Inflammatory Markers and Progression of Coronary Artery Calcification in Adults With and Without Type 1 Diabetes - Alman, Amy C.; Kinney, Gregory L.; Tracy, Russell P.; Maahs, David M.; Hokanson, John E.; Rewers, Marian J.; Snell-Bergeon, Janet K. (Diabetes care, 2013)
The role of inflammation in the increased risk of cardiovascular disease in type 1 diabetes is unclear. We examined the association of inflammation and progression of coronary artery calcification (CAC)-a marker of subclinical atherosclerosis-in adults with and without type 1 diabetes. A nested case-control study was performed within the prospective cohort of the Coronary Artery Calcification in Type 1 Diabetes (CACTI) study. Participants underwent two CAC measurements ~2.5 years apart. Case subjects (n = 204) were those with significant progression of CAC. Control subjects (n = 258) were frequency-matched to case subjects on diabetes status, sex, age, and baseline CAC status. Inflammatory marker assessments were performed on stored blood samples from baseline. A principal components analysis (PCA) was performed and a composite score derived from that analysis. The composite score was constructed by assigning a value of 1 for each PCA component where at least one of the markers exceeded the 75th percentile (range 0-4). Conditional logistic regression was used for the matching strategy. The first two components of the PCA were modestly (odds ratio 1.38 [95% CI 1.08-1.77] and 1.27 [1.02-1.59], respectively) associated with CAC progression after adjustment for other risk factors. The composite score was more strongly associated with CAC progression for those with elevated markers in three or four of the principal components compared with those with none. Measures of inflammation were associated with progression of CAC in a population of adults with and without type 1 diabetes.